The Effects of Knowledge Management on Organization Innovative Performance of SMEs in Kuala Lumpur, Malaysia. The Moderating Impact of Innovation Culture - Kuan, KaiFu (Universiti Malaysia Sarawak (UNIMAS), 2015)
The research is conducted to study the effects ofknowledge management (KM) on organization innovative performance ofSMEs in Kuala Lumpur, Malaysia and how innovation cuhure moderates the relationship between KM and organization innovative performance. The aim of this research was to study the influence of KM dimensions namely knowledge acquisition, knowledge dissemination, knowledge utilization and environmental dynamism on four types of innovative performances, namely product innovation, process innovation, position innovation and paradigm innovation. The innovation cultures used in this research were innovation speed and innovation radicalness. The results revealed that knowledge acquisition and utilization -t did not support organization innovative performance. Environmental dynamism was found fully supporting innovative performance. Knowledge dissemination was found partially supporting innovative performance. Lastly, innovation culture was found partially moderating the relationships between KM and organization innovative performance.